Engineering high-performance and air-stable PBTZT-stat-BDTT-8:PC61BM/PC71BM organic solar cells. Issue 14 (14th March 2018) - Jeon, Il; Sakai, Ryohei; Seo, Seungju; Morse, Graham E.; Ueno, Hiroshi; Nakagawa, Takafumi; Qian, Yang; Maruyama, Shigeo; Matsuo, Yutaka
Abstract : PBTZT-stat-BDTT polymer tolerates water after PEDOT:PSS hole-transport layer coating and blends with mixed C60 /C70 derivative acceptors to give high air-stability and high performance. Abstract : High-performance air-stable PBTZT-stat-BDTT-8 organic solar cells were fabricated using mixed C60 /C70 fullerene acceptors. Normal-architecture devices using PBTZT-stat-BDTT-8 with PC71 BM produced a power conversion efficiency (PCE) of 9.38%. An inverted-architecture, which possesses higher stability, was fabricated using a more economical PC61 BM and PC71 BM mixture with solution-processed PEDOT:PSS on top and produced a PCE of 8.15%. Exploiting the viscous nature of PBTZT-stat-BDTT-8, the slow evaporation effect was utilised to achieve an even higher efficiency of 8.73%. A stability test was conducted under operating conditions and our devices showed remarkably higher stability compared with PTB7-based devices.